Immune Modulating Theorem of Vijaya Ghrita, A Fast Acting Ayurvedic Cannabis Formulation for Treating Covid-19 Disease Symptoms - Ram, G Siva (International Research Journal of Ayurveda & Yoga, 2024)
Covid-19 is an infectious disease caused by airborne virus SARS-CoV-2 was declared as global pandemic by WHO on 11th March 2020. Medical community is facing challenges in developing anti-viral medicines and vaccines, as various mutations in novel coronal virus are causing hurdles in formulating an effective remedy. Environment is crowded with many microorganisms including pathogens like virus, bacteria, fungi, parasites etc. Hence immunomodulation (redirecting immunity to natural course) is the best way to tackle such pandemic situations. Ayurveda, the Indian system of medicine is the oldest science known to mankind has quite a few medicines and therapies to improve immune system. Vijaya (Cannabis sativa Linn.) is the one of the Divyaushadhi (celestial plant) mentioned in Ayurveda having Rasayana (Rejuvenative), Vyavayi (fast diffusing) and Yogavahi (synergetic) attributes. On the basis of Ayurvedic principles we made an attempt to interpret the immune modulating aspect of a rare Cannabis formulation Vijaya Ghrita, presumed to be liposomal medication that has swift bio-enhancing ability. Ayurvedic properties of the ingredients of Vijaya Ghrita found in classical texts could treat most of the symptoms of Covid-19 disease and the contemporary scientific researches of Cannabis phytochemicals on Covid-19 have shown significant results in reducing the pro-inflammatory cytokine storm, also to certain range halt the entry, replication of SARS-CoV-2.